1999
DOI: 10.1097/00001756-199906030-00011
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI study of auditory and visual oddball tasks

Abstract: To seek neural sources of endogenous event-related potentials, brain activations related to rare target stimuli detection in auditory and visual oddball tasks were imaged using a high temporal resolution functional MRI technique. There were multiple modality specific and modality non-specific activations. Auditory specific activations were seen in the bilateral transverse temporal gyri and posterior superior temporal planes while visual specific activations were seen in the bilateral occipital lobes and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
55
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 7 publications
14
55
0
Order By: Relevance
“…As in our study, Due and colleagues, using a similar design, observed activation in prefrontal gyrus and fusiform gyrus and a statistical trend toward activation in anterior cingulate cortex (Due et al 2002). We observed group-level activation in posterior fusiform and lingual gyrus, both extrastriate visual cortical areas and part of a visuospatial attention circuit including anterior cingulate cortex and prefrontal cortex (Kirino et al 2000;McCarthy et al 1997;Saito et al 2003;Yoshiura et al 1999). Despite differences in paradigm design, the convergence of findings amongst smokers in both studies reinforces the notion posed by Due and colleagues that mesocorticolimbic and visuospatial-attention circuits may work in concert to increase attention to stimuli of heightened salience such as the sight of a burning cigarette to an addicted smoker.…”
Section: Discussionsupporting
confidence: 85%
“…As in our study, Due and colleagues, using a similar design, observed activation in prefrontal gyrus and fusiform gyrus and a statistical trend toward activation in anterior cingulate cortex (Due et al 2002). We observed group-level activation in posterior fusiform and lingual gyrus, both extrastriate visual cortical areas and part of a visuospatial attention circuit including anterior cingulate cortex and prefrontal cortex (Kirino et al 2000;McCarthy et al 1997;Saito et al 2003;Yoshiura et al 1999). Despite differences in paradigm design, the convergence of findings amongst smokers in both studies reinforces the notion posed by Due and colleagues that mesocorticolimbic and visuospatial-attention circuits may work in concert to increase attention to stimuli of heightened salience such as the sight of a burning cigarette to an addicted smoker.…”
Section: Discussionsupporting
confidence: 85%
“…In experiments that require subjects to respond to rare target images within a stochastic sequence, activation has been reported in the anterior cingulate, prefrontal, and extrastriate visual cortices during target detection (15)(16)(17)(18). These areas were also activated by the targets within our study.…”
Section: Visuospatial Attention Circuitsupporting
confidence: 67%
“…The visuospatial-attention circuit includes the dorsolateral and ventrolateral prefrontal cortex (inferior frontal gyrus and middle frontal gyrus), anterior cingulate, parietal cortex (intraparietal sulcus), and extrastriate visual cortex (fusiform gyrus). Human functional imaging studies have identified these areas as being activated by rare targets during detection tasks (15)(16)(17)(18). We therefore postulated that visual smoking cues would activate these areas preferentially in nicotine-deprived smokers.…”
Section: Discussionmentioning
confidence: 98%
“…Rare target stimuli are well known to activate a large network of regions as revealed by studies using SEEG [Brázdil et al, 1999;Baudena et al, 1995;Halgren et al, 1998] and fMRI (Brázdil et al, 2005;Clark et al, 2000;Kiehl et al, 2001Kiehl et al, , 2005Stevens et al, 2000;Yoshiura et al, 1999]. Specifically, P3a potential of oddball tasks is unambiguously generated in frontoparietocingulate system, namely in dorsolateral PFC, supramarginal gyrus and cingulate gyrus [Halgren et al, 1998].…”
Section: Discussionmentioning
confidence: 99%